Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acscatal.7b02909
|View full text |Cite
|
Sign up to set email alerts
|

Rh(II)/Pd(0) Dual Catalysis: Regiodivergent Transformations of Alkylic Oxonium Ylides

Abstract: A Rh­(II)/Pd(0) dual-catalysis strategy that promotes the regio-divergent transformations of alkylic oxonium ylides from α-diazo-β-ketoesters has been developed. Polyfunctionalized dihydrofuran-3-ones with an O-substituted quaternary carbon center and 2,3-disubstituted benzofurans can be selectively obtained in good to excellent yields at room temperature via one-pot synthesis. The reaction mechanism was further investigated by the control, stepwise, and crossover experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…In their work, Ru(II)‐associated enolate intermediate C , which was obtained by Ru(II)‐catalyzed C−H functionalization of 4‐(trifluoromethyl)‐phenyl‐substituted α ‐diazoamide, has undergone Pd(0)‐catalyzed asymmetric allylic alkylation with simple allyl tert ‐butyl carbonate to afford chiral 3‐allyl‐3‐aryl oxindoles in good ee (Scheme b) . We also presented a series of Rh(II)/Pd(0) dual‐catalyzed allylic substitution involving Rh(II)‐carbenoids and π ‐allyl Pd(II) intermediates . In recent, we developed a synergistic Rh(II)/Pd(0) dual‐catalysis that promotes the de‐alkylated allylation of Rh(II)‐associated alkylic oxonium ylides D from α ‐diazo‐ β ‐keto‐esters with functionalized π‐ allyl Pd(II) intermediates E , accomplishing the synthesis of highly functionalized dihydrofuran‐3‐one derivatives with an O ‐substituted quaternary carbon center(above, Scheme c) .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In their work, Ru(II)‐associated enolate intermediate C , which was obtained by Ru(II)‐catalyzed C−H functionalization of 4‐(trifluoromethyl)‐phenyl‐substituted α ‐diazoamide, has undergone Pd(0)‐catalyzed asymmetric allylic alkylation with simple allyl tert ‐butyl carbonate to afford chiral 3‐allyl‐3‐aryl oxindoles in good ee (Scheme b) . We also presented a series of Rh(II)/Pd(0) dual‐catalyzed allylic substitution involving Rh(II)‐carbenoids and π ‐allyl Pd(II) intermediates . In recent, we developed a synergistic Rh(II)/Pd(0) dual‐catalysis that promotes the de‐alkylated allylation of Rh(II)‐associated alkylic oxonium ylides D from α ‐diazo‐ β ‐keto‐esters with functionalized π‐ allyl Pd(II) intermediates E , accomplishing the synthesis of highly functionalized dihydrofuran‐3‐one derivatives with an O ‐substituted quaternary carbon center(above, Scheme c) .…”
Section: Figurementioning
confidence: 99%
“…We also presented a series of Rh(II)/Pd(0) dual‐catalyzed allylic substitution involving Rh(II)‐carbenoids and π ‐allyl Pd(II) intermediates . In recent, we developed a synergistic Rh(II)/Pd(0) dual‐catalysis that promotes the de‐alkylated allylation of Rh(II)‐associated alkylic oxonium ylides D from α ‐diazo‐ β ‐keto‐esters with functionalized π‐ allyl Pd(II) intermediates E , accomplishing the synthesis of highly functionalized dihydrofuran‐3‐one derivatives with an O ‐substituted quaternary carbon center(above, Scheme c) . A series of elegant studies by Hu,– Gong, and Zhou demonstrated that zwitterionic intermediates, which were firstly proposed by Doyle et al .…”
Section: Figurementioning
confidence: 99%
“…Therefore, efficient and enantioselective methods to construct such scaffolds are desirable. Progress in this area has mainly come from transition-metal-catalyzed C-H bond activations [21][22][23]. Metal-free catalytic approaches have been much less explored.…”
Section: Introductionmentioning
confidence: 99%
“…[7] a-Quaternary N-heterocycles,i np articular 2-aryl proline derivatives,a re highly valuable and have been utilized in pharmaceuticals and lead compounds. [9] Diazo compounds have found significant application in heterocycle synthesis, [10,11] with XÀHa nd CÀHi nsertion reactions being used to effect cyclization. [9] Diazo compounds have found significant application in heterocycle synthesis, [10,11] with XÀHa nd CÀHi nsertion reactions being used to effect cyclization.…”
mentioning
confidence: 99%
“…[8] Thes ynthesis of these derivatives remains difficult and lengthy,a nd scope is limited, especially for the installation of electron-rich aromatic groups and access to 4-, 6-or 7-membered analogues. [9] Diazo compounds have found significant application in heterocycle synthesis, [10,11] with XÀHa nd CÀHi nsertion reactions being used to effect cyclization. [12] In 2014, as part of our fragment-oriented synthesis program, we reported the use of diazo compounds in an O-H insertion to construct the cyclization precursor for preparation of diverse 2,2-disubstituted oxetane derivatives.…”
mentioning
confidence: 99%